An experimental evaluation of ice cover effects on the dynamic behaviour of a concrete gravity dam. - Paultre, Patrick (Earthquake engineering & structural dynamics.)
An extensive forced vibration testing programme has been carried out on an 84 m concrete gravity dam located in northeastern Quebec, Canada. The dam was subjected to a harmonic load on the crest in summer and severe winter conditions with temperatures ranging from 10 degree celcius to 15 degree celcius and a 1.0-1.5 m ice cover. Acceleration and hydrodynamic frequency responses were obtained in different locations on the dam and in the reservoir. The main objective of the repeated tests was to investigate the effects of the ice cover on the dynamic behaviour of the dam reservoir foundation system, by comparing summer and winter results. Modifications in damping and resonance frequencies were observed, as well as an additional resonance that was attributed to an interaction of the dam with the ice cover. These findings provided a reliable and unique database for the investigations of dam reservoir foundation interaction and, in particular, the ice cover effects for dams located in northern regions.